Distinct effects of Lactobacillus plantarum KL30B and Escherichia coli 3A1 on the induction and development of acute and chronic inflammation - Strus, Magdalena (Cent Eur J Immunol, 2016)
OBJECTIVE: Enteric bacteria are involved in the pathogenesis of ulcerative colitis. In experimental colitis, a breakdown of the intestinal epithelial barrier results in inflow of various gut bacteria, induction of acute inflammation and finally, progression to chronic colitis. MATERIAL AND METHODS: In the present study we compared pro-inflammatory properties of two bacterial strains isolated from human microbiome, Escherichia coli 3A1 and Lactobacillus plantarum KL30B. The study was performed using two experimental models of acute inflammation: peritonitis in mice and trinitrobenzenesulfonic acid (TNBS)-induced colitis in rats. RESULTS: Both bacterial strains induced massive neutrophil infiltration upon injection into sterile peritoneal cavity. However, peritoneal exudate cells stimulated in vitro with E. coli 3A1, produced far more nitric oxide, than those stimulated with L. plantarum KL30B. Interestingly, distinct effect on the development of TNBS-induced colitis was observed after oral administration of the tested bacteria. Lactobacillus plantarum KL30B evoked strong acute colitis. On the contrary, the administration of E. coli 3A1 resulted in a progression of colitis to chronicity. CONCLUSIONS: Our results show that distinct effects of bacterial administration on the development of ongoing inflammation is strain specific and depends on the final effect of cross-talk between bacteria and cells of the innate immune system.